2013
DOI: 10.1521/aeap.2013.25.5.363
|View full text |Cite
|
Sign up to set email alerts
|

Project Salud: Efficacy of a Community-Based HIV Prevention Intervention for Hispanic Migrant Workers in South Florida

Abstract: Project Salud evaluates the efficacy of a community-based intervention to reduce risk behaviors and enhance factors for HIV-preventative behaviors. A randomized controlled trial of 278 high risk Latino migrant workers was conducted between 2008 and 2010. Participants completed an audio computer-assisted self-interview questionnaire at baseline and 3- and 9-month post-intervention follow-ups. Participants were randomly assigned to the community-based intervention (A-SEMI) or the health promotion condition (HPC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
24

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 34 publications
0
20
0
24
Order By: Relevance
“…Our findings supported this prediction. Previous studies have shown that interventions that rely on peer counseling, lay health advisors, and population opinion leaders, such as HoMBReS-2 (Rhodes et al, 2011) and A-SEMI (Sánchez, De La Rosa, & Serna, 2013), are effective to reach, and reduce risk behaviors, among low-acculturated Latino im/migrants in the U.S. (Rhodes, Hergenrather, Bloom, Leichliter, & Montaño, 2009; Somerville, Diaz, Davis, Coleman, & Taveras, 2006; Vissman et al, 2009). In contrast, and as predicted by our second study hypothesis, exposure through mass media (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings supported this prediction. Previous studies have shown that interventions that rely on peer counseling, lay health advisors, and population opinion leaders, such as HoMBReS-2 (Rhodes et al, 2011) and A-SEMI (Sánchez, De La Rosa, & Serna, 2013), are effective to reach, and reduce risk behaviors, among low-acculturated Latino im/migrants in the U.S. (Rhodes, Hergenrather, Bloom, Leichliter, & Montaño, 2009; Somerville, Diaz, Davis, Coleman, & Taveras, 2006; Vissman et al, 2009). In contrast, and as predicted by our second study hypothesis, exposure through mass media (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The present cross-sectional study is part of a larger study funded by the National Institutes of Health (NIH) entitled "HIV Risk Reduction among Hispanic Migrant Workers in South Florida," which employed an interventional design. 17 From June 2008 through June 2011, outreach workers screened 407 Hispanic farmworkers who were recruited by means of a stratified network-based (snowball) sampling design from neighborhoods and migrant camps in the Homestead/Florida City area in South Florida, which is known for its high concentration of Hispanic farmworkers. 18 The present investigation is based on 278 study participants out of the 290 potential participants that met eligibility criteria.…”
Section: Methodsmentioning
confidence: 99%
“…In the second trial concerning sexually transmitted diseases [49], a community-based participatory research project, the "Project Salud", was presented with the aim of involving the Latin American community in Florida for the prevention of HIV. The main objective of the "Salud Project" is to compare and evaluate the effectiveness of 2 different methods: the so-called "Adapted Stage-Enhanced Motivational Interviewing (A-SEMI), divided into 4 group sessions to prevent HIV and encourage safe sexual behavior, and the "Health Promotion Condition" (HPC), aimed at promoting public health strategies, such as hygiene and first aid.…”
Section: Trialmentioning
confidence: 99%